2016
DOI: 10.5430/ijhe.v5n4p157
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Histology Lectures and Practical Teaching in China

et al.

Abstract: Objectives: Human histology is a discipline concerning the study of microscopic structures of human tissues and organs -with the aid of light or electron microscopes. Traditional teaching of histology is composed of two separated components, theory and practice. The main disadvantage with traditional histology teaching is the detachment of theory and practice, so that students could not completely and systematically comprehend histology. Methods: To supplement the deficiencies of traditional histology teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…This result shows that the determinant coefficient is adjusted R square = 0,507 which means the influence of teaching style and learning behavior toward student achievement is 50,7%, the rest 49,3% influenced by other factors like physical condition, talent, interest, intelligence, motivation and others. The results showed that: There is a positive and significant effect between teaching style lecturers and learning behaviour towards on the student achievement The results of this study also supported by research conducted by Lu, et al (2016) states that the students' perceptions of how to teach teachers during learning will increase the interaction between teachers and students so as to improve student semester test results. Also research conducted by Erdogan, Bayram, and Deniz (2008) states that students' attitudes in addressing their environment will increase their exposure to learning outcomes that spur students to act actively in learning.…”
Section: Effect Of Teaching Style Of Lecturer and Student Learning Besupporting
confidence: 77%
“…This result shows that the determinant coefficient is adjusted R square = 0,507 which means the influence of teaching style and learning behavior toward student achievement is 50,7%, the rest 49,3% influenced by other factors like physical condition, talent, interest, intelligence, motivation and others. The results showed that: There is a positive and significant effect between teaching style lecturers and learning behaviour towards on the student achievement The results of this study also supported by research conducted by Lu, et al (2016) states that the students' perceptions of how to teach teachers during learning will increase the interaction between teachers and students so as to improve student semester test results. Also research conducted by Erdogan, Bayram, and Deniz (2008) states that students' attitudes in addressing their environment will increase their exposure to learning outcomes that spur students to act actively in learning.…”
Section: Effect Of Teaching Style Of Lecturer and Student Learning Besupporting
confidence: 77%
“…Once normal structure is known then a student can appreciate pathological change in structure 12 . Students should have a clear concept about the structure of normal humancells & tissue for future clinical application 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Although curriculum planning and teaching strategies are decided by the faculty but the opinion of the students need to be taken into account during curriculum making to get out the best outcome 9 . There is some detachment seen between the theory and practice, due to which the students face problems in comprehending histology systemically 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Some HE teachers in Malaysia have compiled new manuals to incorporate histological images with clinical correlates (Ansari et al, 2018), and other teachers in the United States have integrated histological theoretical lectures with practice sessions by including clinical cases by digital images and videos in the same classroom setting (Diaz‐Perez et al, 2014). Chinese teachers have reported the simultaneous integration of histological didactic lectures with practice sessions, which has produced better learning outcomes by removing the temporal‐spatial barriers that existed in traditional teaching (Lu et al, 2016). These changes keep up with the general trends that are being followed as medical schools make significant curricular changes, moving from educational programs consisting of discipline‐based courses to integrated curricula, which has been outlined and suggested by experienced anatomical educators (Drake, 1998; Drake, 2014).…”
Section: Discussionmentioning
confidence: 99%